Tunica vaginalis flap – is it a better surgical choice for urethro-cutaneous fistula following circumcision? - krishnendu maity; Pinaki roy; Dilip Kumar Pal (International Journal of Medical Research and Review, 2020)
Objective: To study the effectiveness of tunica vaginalis flap in repair of post circumcision urethro- cutaneous fistula.Materials and Methods: The current study reviewed all patients having surgical repair of post-circumcision urethrocutaneous fistula from December 2014 to April 2019 at our institution.Results: Ten cases presenting at age 5 to 22 years were operated. Most [60%] of the circumcisions were performed by a doctor at peripheral hospitals and others were done by traditional circumcisers. All cases had a single fistula and the size was more than 5mm in all cases. Three-layered fistula closure was done in all cases using the tunica vaginalis flap as the second layer for closure. There was no recurrence in any case.Conclusion: Use of Tunica vaginalis flap for repair of post circumcision urethro-cutaneous fistula is a highly effective technique regardless of size and site of the fistula. It is a simple procedure without any postoperative complications and without any recurrence